2001
DOI: 10.1111/j.1559-1816.2001.tb01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Auditory Message Framing Effects on Tobacco Smoking1

Abstract: Persuasive health messages can be framed to emphasize the benefits of adopting a health behavior (gains) or the risks of not adopting it (losses). This study examined the effects of message framing on beliefs, attitudes, and behaviors relevant to cigarette smoking. In video presentations about tobacco smoking, visual images and auditory voiceover content were framed either as gains or losses, yielding 4 message conditions. Undergraduates ( N = 437) attending a public university in New England were assigned ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 23 publications
11
101
0
1
Order By: Relevance
“…Schneider, Salovey, Pallonen, et al (2001) noted a decrease in number of cigarettes smoked among participants who received gain-framed messages, and Steward et al (2003) reported greater intentions to quit among participants in the gain-framed condition. In our report, the measure of time to the first cigarette was more sensitive to message framing effects than categorical outcomes.Taken together with prior findings (Schneider, Salovey, Pallonen, et al, 2001;Steward et al, 2003), the results of this study are consistent with the hypothesis that messages promoting smoking cessation are more persuasive if they emphasize the gains associated with quitting smoking rather than the losses associated with continued smoking, although the advantage of gain-framing was not as robustly observed here as compared with previous studies. Future studies should examine whether integrating gain-framed messages into counseling protocols can enhance these effects.…”
mentioning
confidence: 94%
“…Schneider, Salovey, Pallonen, et al (2001) noted a decrease in number of cigarettes smoked among participants who received gain-framed messages, and Steward et al (2003) reported greater intentions to quit among participants in the gain-framed condition. In our report, the measure of time to the first cigarette was more sensitive to message framing effects than categorical outcomes.Taken together with prior findings (Schneider, Salovey, Pallonen, et al, 2001;Steward et al, 2003), the results of this study are consistent with the hypothesis that messages promoting smoking cessation are more persuasive if they emphasize the gains associated with quitting smoking rather than the losses associated with continued smoking, although the advantage of gain-framing was not as robustly observed here as compared with previous studies. Future studies should examine whether integrating gain-framed messages into counseling protocols can enhance these effects.…”
mentioning
confidence: 94%
“…Schneider and colleagues 11 found that gain-framed health messages (for example, "Quitting smoking reduces your chances of premature death and illness") were more effective than the same messages rewritten so that they were loss-framed (for example, "Smoking increases your chances of premature death and illness") in changing smoking related beliefs, attitudes, and behaviours.…”
Section: Utilise Gain-framed Messagesmentioning
confidence: 99%
“…These results conflict with data from other studies using a visual reminder. Previous research has shown that both positively and negatively phrased visual messages can affect health related behaviors and attitudes, specifically related to smoking [19]. In their work, subjects' attitudes toward smoking as well as cigarette consumption improved with either phrased message, but more so with positively worded messages.…”
Section: Hba1cmentioning
confidence: 84%
“…However, this technique has been evaluated in areas such as sunscreen use, smoking cessation, and dieting [17][18][19]. The literature is lacking in terms of evaluating this technique in the application of a disease management program or with T2DM as the focus.…”
Section: Introductionmentioning
confidence: 99%